Integrating machine learning and digital microfluidics for screening experimental conditions. Issue 1 (23rd November 2022) - Ahmadi, Fatemeh; Simchi, Mohammad; Perry, James M.; Frenette, Stephane; Benali, Habib; Soucy, Jean-Paul; Massarweh, Gassan; Shih, Steve C. C.
Abstract : A new approach to combine digital microfluidics and machine learning algorithms to enable applications that require high throughput analysis. Abstract : Digital microfluidics (DMF) has the signatures of an ideal liquid handling platform – as shown through almost two decades of automated biological and chemical assays. However, in the current state of DMF, we are still limited by the number of parallel biological or chemical assays that can be performed on DMF. Here, we report a new approach that leverages design-of-experiment and numerical methodologies to accelerate experimental optimization on DMF. The integration of the one-factor-at-a-time (OFAT) experimental technique with machine learning algorithms provides a set of recommended optimal conditions without the need to perform a large set of experiments. We applied our approach towards optimizing the radiochemistry synthesis yield given the large number of variables that affect the yield. We believe that this work is the first to combine such techniques which can be readily applied to any other assays that contain many parameters and levels on DMF.